Residential proximity to major roadways and hearing impairment in Chinese older adults: a population-based study - Xingxing Chen; Jun Wang; Xian Zhang; Gui Xiao; Siran Luo; Lei Liu; Weijia Kong; Xiaomin Zhang; Lijing L. Yan; Sulin Zhang (BMC, 2023)
Abstract Background With rapid urban sprawl, growing people are living in the vicinity of major roadways. However, little is known about the relationship between residential proximity to major roadways and hearing impairment (HI). Methods We derived data from the 2018 wave of the Chinese Longitudinal Healthy Longevity Survey, and included 13,775 participants aged 65 years or older. Multivariate logistic regressions were employed to examine the association between residential proximity to major roadways and HI. The effects of corresponding potentially modifiable factors were studied by three-way interaction analyses. Sensitivity analyses were performed to verify the robustness of the results. Results The prevalence of HI was 38.3%. Participants living near major roadways were more likely to have a higher socioeconomic status. An exposure-response relation between residential proximity to major roadways and HI was observed (P trend < 0.05). Compared with individuals living > 300 m away from major roadways, the adjusted odds ratios (OR) were 1.07 (95% CI: 0.96-1.24), 1.15 (95% CI: 1.07-1.34), and 1.12 (95% CI: 1.01-1.31) for those living 101-200 m, 50-100 m, and < 50 m away from the roadways, respectively. Particularly, the association was more pronounced among individuals exposed to carbon monoxide (CO) pollution or opening windows frequently (P interaction < 0.05). Three-way interaction analyses confirmed that participants exposed to CO pollution and frequently leaving windows open had the highest OR of 1.73 (95% CI: 1.58-1.89). Conclusions This nation-wide cohort study suggested that residential proximity to major roadways was significantly associated with an increased exposure-response risk of HI in Chinese older adults. Exposure to CO pollution and opening windows frequently might strengthen the relations.